World Literature and Dissent - Burns, Lorna; Muth, Katie (Taylor & Francis, 2019)
World Literature and Dissent reconsiders the role of dissent in contemporary global literature. Bringing together scholars of world and postcolonial literatures, the contributors　explore the aesthetics of resistance through concepts　including　the epistemology of ignorance, the rhetoric of innocence, the subversion of paying attention, and the radical potential of everydayness.　　 　 Addressing a broad range of examples, from the　Maghrebian　humanist Ibn Khaldūn to India's Facebook poets and examining writers such as Langston Hughes, Ben　Okri, Sara Uribe, and Merle Collins, this highly relevant book reframes the field of world literature in relation to dissenting politics and aesthetic.　 It asks the urgent question:　how critical practice might　cultivate　radical thought, further social justice, and value human expression?